Unravelling keyhole instabilities and laser absorption dynamics during laser irradiation of Ti6Al4V: A high-fidelity thermo-fluidic study - Aggarwal, Akash; Shin, Yung C.; Kumar, Arvind (International journal of heat and mass transfer, 2024)
•High-fidelity modeling to investigate melt pool dynamics and keyhole instabilities.•Investigation of keyhole closure mechanism and bubble trapping-ejection phenomena.•Results reveal direct correlation of laser absorptance with keyhole depression depth.•Keyhole regime show substantial oscillations (periodic and non-periodic).•Modeling validation with in-house performed laser melting measurements. A 3D multi-phase thermo-fluidic solver is implemented to investigate the laser-melt pool interaction dynamics and keyhole instabilities during stationary and moving laser irradiation. The physical phenomena such as phase changes, thermocapillary driven flow, multiple reflections of the Gaussian laser beam and beam trapping, vaporization recoil pressure, and heat losses (convective, radiative, and evaporative) have been incorporated in the model. A detailed parametric study has been carried out to investigate the influence of the laser beam spot diameter and the traversal speed on the laser absorption dynamics and melt pool characteristics. For both the stationary and moving laser irradiation, it is found that during the initial transient stage, the melt pool morphology belongs to the conduction melting mode with laser absorption according to the normal incidence condition of the Fresnel equation. Later, depending on the irradiating laser intensity, a melt transition occurs from conduction to the keyhole mode of melting, during which laser absorption rises sharply. The laser absorption and the vapor depression morphology in the keyhole regime show substantial oscillations (periodic and non-periodic) due to the complex hydrodynamics of the recoil pressure, the surface-tension dynamics, and convection-driven flow resulting in the opening and closing of the vapor depression. These oscillations are quantified, and a direct correlation of the laser absorptance with the keyhole depression depth has been observed for stationary laser irradiation. The keyhole closure mechanism and bubble trapping-ejection phenomena have been explored during the solidification stage. The numerically predicted melt pool dimensions match well with the in-house performed experimental measurements and published benchmarking experiments combining integrating sphere radiometry and in-situ X-ray radiography. [Display omitted]